Implementation of JQH Santri Al-Qur'an Memorization Activities for IDIA Prenduan Girls, Al-Amien University (UNIA), Prenduan - Ismayani; Abdul Muiz (Penerbit Hellow Pustaka, 2025)
The Qur'an is an eternal miracle from Allah SWT whose truth is increasingly proven as science develops. In Indonesia, the tradition of memorizing the Qur'an has been going on for a long time and is growing rapidly, especially through Islamic boarding schools founded by clerics who have memorized the Qur'an. This research aims to examine the implementation of Al-Qur'an memorization activities among JQH Putri IDIA Prenduan students. The method used in this research is a qualitative approach with a type of field research, which collects data through observations and interviews. The research results show that the Al-Qur'an memorization program at JQH Putri IDIA Prenduan is implemented using various methods, such as sorogan and face-to-face methods, as well as a minimum target of one verse per day. Supporting factors in memorizing activities include the influence of good friends, adequate facilities, and a conducive environment, while inhibiting factors include laziness, impatience, and lack of seriousness among students. In conclusion, the implementation of memorizing the Al-Qur'an at JQH Putri IDIA Prenduan is going well, although there are several obstacles that need to be considered to increase the effectiveness of the memorization program.